Prevalence of 563 C – T& 131 C-G G6PD polymorphisms in term and late preterm neonates with significant unconjugated hyperbilirubinemia from a tertiary level care neonatal unit in Uttarakhand: G6PD polymorphisms in neonates - Chacham, Swathi; Chaudhary, Yatika; Naithani, Manisha; Bhakat, Rahul; Rajput, Swati; Kumar Verma, Prashant; Basu, Sriparna; Mohan, Kriti (Indian Journal of Child Health, 2024)
Objectives: This study aimed to estimate the frequency of Glucose-6-phosphate dehydrogenase (G6PD) Mediterranean variant (563 C->T) and G6PD Odisha (131 C->G) variants along with the prevalence of G6PD deficiency quantitatively. This study also estimated peak serum total bilirubin level and duration of phototherapy and correlated with the G6PD levels and G6PD mutations.Methods: All the consecutive term and late pre-term neonates of either gender with significant hyperbilirubinemia were enrolled after written informed consent and were screened for G6PD deficiency (quantitatively). These neonates were also evaluated for G6PD gene polymorphisms.Exclusion criteria: Neonates with congenital anomalies or conjugated hyperbilirubinemia and those who received treatment before enrollment were excluded from this study.Results: A total of 150 infants with hyperbilirubinemia were enrolled. Males were two-thirds. Median G6PD levels were 11.9 units/gm of Hb (Inter quartile range [IQR]: 9.4–16.2). The prevalence of G6PD deficiency in our study population was 24% among the whole population and 30.6% in male infants. As per the World Health Organization (WHO) classification, majority (94%) were in class IV, 5.3% (n=8) had WHO Class III. All the eight infants in Class III were males. Mean (SD) and median serum bilirubin levels were 16.7 (1.1) mg/dL. Median duration of phototherapy was 24 h. Gene polymorphisms were done in 119 neonates. G6PD Mediterranean mutations were seen in 6.7% and G6PD Orissa mutations were seen in 4.2% neonates. There was a good correlation between G6PD deficiency and serum total bilirubin, mean duration of phototherapy and gender.Conclusion: This study reported 24% prevalence of G6PD deficiency among the study population with 6.7% prevalence of G6PD Mediterranean mutations and 4.2% prevalence of G6PD Orissa mutations.